Guardians of the nightlife: a sociological exploration of bouncers and dancers in exotic dance clubs - Deshotels, Tina H. (Deviant behavior, 2025)
This paper examines the primary agent of social control in strip clubs: the bouncer. It discusses the bouncer’s various roles, including gatekeeping, controlling patron behavior, managing dancer behavior in different club settings, and enforcing all rules of conduct. Additionally, it explores lesser-known roles that generate income for both bouncers and dancers, such as the relationship between rules and bouncer behavior, and the scheduling of regular clients for exotic dancers. The research is based on over 200 interviews conducted with bouncers and dancers at all levels of clubs between 1993 and 2023 across several states.